PENGARUH FOMO DAN INTENSITAS PENGGUNAAN TIKTOK TERHADAP IDENTITAS DIRI GENERASI Z - Isfah Ayu Faradillah,; Ni Nyoman Sri Wisudawati, (Journal of Innovation Research and Knowledge, 2025)
TikTok has become one of the most influential digital platforms shaping the behavior and identity formation of Generation Z. The rise of the Fear of Missing Out (FoMO) phenomenon encourages individuals to remain constantly connected to online social activities. This study aims to examine the effect of FoMO on self-identity, as well as the mediating role of TikTok usage intensity. A quantitative approach was employed using purposive sampling, involving 100 Generation Z respondents residing in Denpasar City. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) through SmartPLS 3. The findings indicate that FoMO has a positive and significant effect on self-identity (p = 0.000) and TikTok usage intensity (p = 0.000). Usage intensity also significantly influences self-identity (p = 0.030). Furthermore, usage intensity was proven to mediate the relationship between FoMO and self-identity (p = 0.002). These results suggest that FoMO plays a dominant role in shaping the digital identity of Generation Z, while usage intensity strengthens this process. The study contributes to digital communication research and provides practical insights for promoting more mindful social media engagement